THE INFLUENCE OF PUBLIC DIPLOMACY IN G20 2022 SUMMIT IN INDONESIA’S POST-PANDEMIC TOURISM AND ECOTOURISM RECOVERY EFFORTS - Rozanah, Astri; Ishqila, Nurul Athiya (Universitas Nasional, 2024)
The COVID-19 pandemic has caused a number of countries to implement blockade policies to limit its spread, including Indonesia, which has implemented a large-scale containment social restraint policy (PSBB). This study uses a qualitative descriptive research method to describe, explain, and answer the problems studied for social phenomena in detail. The theory is particularly pertinent to the G20 Indonesia 2022 tourism diplomacy context, because it can be used to enhance Indonesia's reputation as a tourist destination and forge alliances with other nations to attract more travelers. The G20 Summit in Bali, Indonesia, had a positive impact on Indonesia, especially tourism and economic recovery through ecotourism. The 2022 G20 summit provided significant economic benefits for Indonesia, helping to recover the economy affected by the Covid-19 virus. This will support efforts to revive the tourism industry after the impact caused by the COVID-19 virus, and fostering a favorable image of the nation internationally. G20 Summit initiatives such as quarantine exemptions for international visitors and reintroduction of visit visas for foreigners have resulted in a potential increase in foreign tourist interest of 83.55%. This makes a significant contribution to the Indonesian tourism industry, creating new jobs, supporting MSMEs and improving the economy. The result shows that government's efforts to promote tourism, including the Proud to Travel Indonesia campaign, aim to increasing the interest and pride of the Indonesian people in domestic travel, and the performance target of the tourism industry has been set to US7.39-13.08 billion in foreign exchange production by 2024.